KEDUDUKAN AKTA YANG DIKELUARKAN OLEH NOTARIS YANG SEDANG DALAM MASA TAHANAN - Samuel Dharma Putra Nainggolan; Kholilur Rahman; Abraham Sridjaja; Jamalum Sinambela (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2023)
The notary in carrying out his position must remember that the deed made by or before him is an authentic deed that becomes a document/state archive, and the agreement stated therein becomes a law for those who make it. The important role of a Notary in making a deed is inseparable from the possibility of actions that are contrary to the propriety prevailing in the society in carrying out the duties and functions of a Notary. A notary who is currently in detention as long as he has not been dismissed as a notary is still capable of making an authentic deed, but in terms of propriety, this is not justified. UUJN contains sanctions against Notaries who are proven to have committed violations, during this period the Deeds made downgraded from Authentic Deeds to Underhanded Deeds. This legal research uses a statute approach, a conceptual approach, and a case approach. In this context, it is concluded that the Notary is temporarily dismissed from his position because he is currently undergoing a detention period. After the temporary dismissal period ends due to the detention period, the Notary will be rehabilitated after the temporary dismissal period ends. The rehabilitation in question implies that the notary concerned is activated and returned to his original position. Therefore, if the notary is returned to his original position, the deed made by the notary is authentic. In this case, if the detention period is more than 6 months, while the temporary dismissal period has ended, the notary has authority according to his functions and duties.